Strategi Pemasaran Agen Asuransi Dalam Menumbuhkan Minat Masyarakat Pada Produk Asuransi PT Sunlife - Rifka Fachrina; Nuri Aslami (Jurnal Ilmiah Mahasiswa Perbankan Syariah (JIMPA), 2021)
Fundamentally insurance agencies emerge due to the hazard avoidance conduct of people in general. The dangers experienced by the local area are ailment, passing, misfortune, and harm to products. To conquer this, insurance agencies show up and attempt to limit the misfortunes that will be capable by the local area later on. This review utilizes an illustrative examination strategy, to be specific through the creator portraying the issue dependent on the current information and afterward further investigation to make determinations. The overall procedure utilized by insurance agencies in developing public interest in Sun Medical Platinum health care coverage items is to move toward shoppers. The Sunlife organization centers around focusing on the whole local area fully intent on giving and making great help. What's more, the Sunlife organization is additionally making the most of the current chances.